Effects of three fungal pathogens on water relations, chlorophyll fluorescence and growth of Quercus suber L - Luque, Jordi; Cohen, Moshe; Save, Robert; Biel, Carmen; Álvarez F., Isabel (Ann. For. Sci., 1999)
Some physiological and growth parameters were studied in cork oak plants inoculated with three pathogenic fungi growth, stomatal conductance, air-leaf temperature and photo- (Botryosphaeria stevensii, Hypoxylon mediterraneum and Phytophthora cinnamomi) in order to understand the effects of the fungal infection. All inoculated fungi induced the reduction of daily stem chemical efficiency. The more aggressive pathogens, B. stevensii ans P. cinnamomi, induced the sharpest decline in all growth and physiological parameters. A sudden decline of all variables was caused by B. stevensii within 6 days after inoculation, followed by a temporary increase in maximum daily shrinkage coinciding with wilting of the plants. The plants inoculated with P. cinnamomi underwent a more gradual decrease in all parameters, whereas H. mediterraneum induced a slight but still significant reduction only in stem growth and shrinkage. Linear variable displacement transducers (LVDT) proved to be a suitable tool to measure some effects of the pathogenesis.
Keywords: Botryosphaeria stevensii; hydric stress; Hypoxylon mediterraneum; LVDT; pathogenic effect; phytophthora cinnamomi

PATOGENICIDAD DE HONGOS AISLADOS DEL ALCORNOQUE EN CATALUÑA - LUQUE, J; ÁLVAREZ, I (II Congreso Forestal Español, 1997)
Forty four fungal strains were used in pathogenicity tests made in trunk (32), leaves (8), and roots (8) of cork oak plants (Quereus suber L.) with two irrigation treatments (adequate and stress). Eleven species were found to be pathogenic on tnmk and three on leaf. Trunk pathogens such as Botryosphaeria stevensii, Phytophthora einnamomi, and (?)Diseula sp. caused the death of the inoculated plants. Hydric stress increased both canker and necrosis formation by (?)Diseula sp. and H. mediterraneum, reduced the effects of P. cinnamomi and had no effect on B. stevensii. The latter fungus was a virulent pathogen irrespectively of the irrigation treatment. Dendrophoma myriadea and (?)Fusieoeeum sp. were pathogenic on leaves. Both fungi were negatively affected by the hydric stress. However, no satisfactory results were obtained in the root inoculations. K.W.:
Keywords: Botryosphaeria stevensii; decline; Hypoxylon mediterraneum; pathogenic fungi; phytophthora cinnamomi; Quercus suber

Dieback of cork oak (Quercus suber) in Catalonia (NE Spain) caused by Botryosphaeria stevensii - LUQUE, J; Girbal, J (European Journal of Forest Pathology, 1989)
Botryosphaeria stevensii Shoemaker (anamorph: Diplodia mutila Fr. apud Mont.) is reported as the cause of canker and dieback of cork oak (Quercus suber L.) in Catalonia (NE Spain). It also causes wilting of trees after cork is removed for industrial purposes. Symptomatology and details of morphology for both anamorph and teleomorph are given.
Keywords: Botryosphaeria stevensii; canker; Cork oak; dieback; diplodia mutila; morphology (PG); Symptoms